THE IHIP MODEL IN SPORTS SERVICES MARKETING - Dumitru Iulian; Nichifor Florin; Ungurean Bogdan (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
The challenge of identifying - within well-delimited reference points - the specific of (sports) services has represented a difficult task from the beginning. The general view is that the marketing of goods must be treated in a different manner than that of services, considering the existence of differences between the two fields of study. Our aim was to analyze, from a critical perspective, the IHIP model imposed by the scientific productions that dealt with the marketing of services. The IHIP acronym was coined by three authors, Zeithaml, Parasuraman and Berry [15], who had the initiative of delimiting - out of the generous and relatively vast panel of service characteristics - a four-item model: intangibility, heterogeneity, inseparability, and perishability. Throughout time, the model imposed by the three authors has been subjected to a veritable purgatory. Besides the faithful devotees, enough specialists have demonstrated - through various theories - the inconsistency of the model. The main weak point was represented by the accreditation of the idea that the proposed model was incapable of making a clear distinction between goods and services. This model presents a series of limits and weak points, which turn it into a slightly outdated approach from the perspective of the genesis, systematisation and hierarchy of the "unique" and "specific" characteristics of services in general. The academic discourse and the approaches imposed by practice have demonstrated the need for new paradigms regarding the specificity of the services and the major differences from the physical goods. However, from the didactic perspective and considering the monitoring of (sports) marketing theory and practice, they represent a reference framework that preserves valuable and necessary elements for the new research and approach directions of this issue.